Identification of Activities in the Planning, Conduct, and Control Stages of The Procurement Process based on PMBOK 6th Edition (Case Study: PT X) - Rizqika, Salsabilla; Riantini, Leni Sagita (Avenew Indonesia, 2025)
The procurement of goods and services is a crucial stage before the commencement of construction, and any delays in the procurement process may significantly impact project implementation. PT X is a state-owned enterprise (SOE) in the construction sector, particularly in toll road construction. Based on data from repeated tenders over the past three years, it is evident that the phenomenon of retendering frequently occurs at PT X. This has led to several issues, with the most prominent being delays in contract execution. Therefore, the procurement process currently implemented at PT X needs to be reviewed. The Project Management Body of Knowledge (PMBOK) 6th edition approach is employed to assess whether there are discrepancies between the procurement activities carried out at PT X and those recommended by PMBOK 6th edition that could potentially lead to retendering. This study aims to identify the planning, conduct, and control stages of the procurement process using the PMBOK 6th edition framework. The research method used includes a literature study and questionnaire, which are analyzed qualitatively. The questionnaire was distributed to five experts, comprising academics and practitioners. Based on the data analysis, 16 procurement planning activities, 13 procurement conduct activities, and 12 procurement control activities were identified according to PMBOK 6th edition.